PENGARUH LITERASI DIGITAL DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN DIGITAL BRANDING SISWA KELAS XI BISNIS DIGITAL DI SMK NEGERI 6 MEDAN TAHUN AJARAN 2024/2025 - Sindy Wulandari; Ivo Selvia Agusti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of digital literacy and learning independence on learning outcomes in the Digital Branding subject among Grade XI Digital Business students at SMK Negeri 6 Medan in the 2024/2025 academic year. The research employed a quantitative approach with an ex-post facto method. The sample consisted of the entire population, totaling 67 students, who were all selected as respondents (total sampling). The research instruments included a digital literacy questionnaire, a learning independence questionnaire, and documentation of students’ learning outcomes. Data were analyzed using multiple linear regression with the aid of SPSS version 25. The results showed that digital literacy had a positive and significant effect on learning outcomes (sig. = 0.015 < 0.05), learning independence also had a positive and significant effect on learning outcomes (sig. = 0.008 < 0.05), and simultaneously, both digital literacy and learning independence had a positive and significant effect on students’ learning outcomes, with a coefficient of determination (R²) of 0.640. This means that 64% of the variation in learning outcomes can be explained by digital literacy and learning independence, while the remaining 36% is influenced by other factors outside the study, such as family environment, learning facilities, and peer environment. These findings confirm that good digital literacy and high learning independence contribute significantly to optimal learning achievement.